Rapid Bactericidal Activity of Punica granatum L. Peel Extract: A Natural Alternative for Mastitis Prevention in Dairy Cattle - Carenn Rodrigues e Almeida Silva; Camila Silva Vidal; Sergio Martins de Andrade Filho; Izabela Martins Agatão; Lidiane Coelho Berbert; João Bosco de Salles; Alexander Machado Cardoso; Ricardo Machado Kuster; Cristiane Pimentel Victório; Maria Cristina de Assis (Molecules)
The increasing prevalence of bacterial resistance to conventional disinfectants and antibiotics has intensified the search for effective, natural alternatives in the dairy industry. This study evaluates the bactericidal efficacy of Punica granatum L. (pomegranate) peel ethanolic extract, focusing on its application in pre- and post-dipping procedures for mastitis prevention. The extract exhibited potent activity against Escherichia coli and Staphylococcus aureus, two major mastitis pathogens. At a concentration of 10 mg/mL, the extract induced significant membrane disruption within 30 s of exposure, as evidenced by propidium iodide uptake and elevated extracellular DNA levels (Escherichia coli: 64.25 ng/μL; Staphylococcus aureus: 83.25 ng/μL) compared to controls (11.20 ng/μL and 35.20 ng/μL, respectively; p < 0.05). Complete growth inhibition (100%) was achieved within 30 s at 25 and 50 mg/mL, matching the efficacy of commercial chlorhexidine and high-concentration hypochlorite. Phytochemical analysis identified punicalagin as the predominant bioactive compound. These findings establish Punica granatum peel extract as a fast-acting bactericidal agent, exhibiting an efficacy comparable to or exceeding that of conventional disinfectants. Its rapid action and plant-based origin highlight its potential as a viable alternative for the prevention and control of bovine mastitis in dairy farming.